Description of three new caddisfly species from Mayotte Island, Comoros Archipelago (Insecta: Trichoptera) - Johanson, Kjell Arne; Mary, Nathalie (Zootaxa, 2009)
We report five new species records from the Comoros Archipelago. Two of the species are known from outside the Archipelago, Hydroptila cruciata Ulmer (Hydroptilidae) and Anisocentropus voeltzkowi Ulmer (Calamoceratidae), and three species are described as new to science: Pisulia stoltzei ,new species (Pisuliidae), and: Chimarra mayottensis, new species and Chimarra koulaeensis, new species (Philopotamidae). Five species have been previously recorded from the Comoros Islands: Cheumatopsyche comorina (Navás), Macrostemum capense (Walker), Cheumatopsyche vala Malicky (Hydropsychidae), Hydroptila voticia Malicky (Hydroptilidae), and Oecetis atpomarus Malicky (Leptoceridae). With this report the number of species from the Comoros is doubled. These findings also represent the first records of Trichoptera from Mayotte.